How to promote entrepreneurship within established companies? : human resource management and corporate entrepreneurship - Jockenhöfer, Manuel (Compact., 2013)
Hauptbeschreibung Given the dynamic of today's business environments, more and more established companies attempt to promote entrepreneurship within their organizational boundaries to preserve and reinforce the innovativeness and flexibility from which many young enterprises benefit and so enhance their competitiveness and economic viability. The strategy pursued by them is called a corporate entrepreneurship strategy. This book gives answers on the question of how an organization can strengthen the entrepreneurial mindset and behavior of its employees with the help of appropriate h.